Structural characterization of fibrous synthetic hydrogels using fluorescence microscopy. Issue 17 (15th April 2020) - Vandaele, Johannes; Louis, Boris; Liu, Kaizheng; Camacho, Rafael; Kouwer, Paul H. J.; Rocha, Susana
Abstract : The structural features of the matrix surrounding the cells play a crucial role in regulating their behavior. Abstract : The structural features of the matrix surrounding the cells play a crucial role in regulating their behavior. Here, we used fluorescence microscopy and customized analysis algorithms to characterize the architecture of fibrous hydrogel networks. As a model system, we investigated a new class of synthetic biomimetic material, hydrogels prepared from polyisocyanides. Our results show that these synthetic gels present a highly heterogeneous fibrous network, with pores reaching a few micrometers in diameter. By encapsulating HeLa cells in different hydrogels, we show that a more porous structure is linked to a higher proliferation rate. The approach described here, for the characterization of the network of fibrous hydrogels, can be easily applied to other polymer-based materials and provide new insights into the influence of structural features in cell behavior. This knowledge is crucial to develop the next generation of biomimetic materials for 3D cell models and tissue engineering applications.